Development of a High Hertz-Stress Contact for conventional batch production using a unique scribing technology - Bhuiyan, Md. Moinul Islam; Rashid, Muhammad Mahbubur; Alamgir, Tarik; Bhuiyan, Munira; Kajihara, Masanori (2013)
Gradually the electronic devices are getting more compact dimension with respect to the width and thickness. As a result, the contacts are becoming thinner and which leads the contact to be loose and unstable contact. In comercial stamping methode, connector tip diameter should be more than 300μm due to its size limitation. Consequently, the connector contact resistance is becoming higher due to weak contact force. To overcome this problem there were few more basic research using MEMS and Electro Fine Forming (EFF) technology to make high Hertz-Stress Contact (5μm) due to the limitation in the commercial stamping process and the result was in satisfactory level. However, since the MEMS and EFF fabrication is costly therefore, a new method is introduced in this paper using the commercial Phosphor Bronze stamping method to reduce the production cost. Moreover, scribing method is used to make tip on the contact. Accordingly, more compact fine pitch contact is successfully fabricated and tested with 5μm High Hertz Stress without using the MEMS and EFF technology. Hence the manufactured contact resistance becomes less than 20mΩ ±5mΩ.